Detection rate and clinical significance of latent infective endocarditis in patients with aortic stenosis - O. B. Irtyuga; V. I. Chistyakova; A. O. Tenchurina; V. N. Solntsev; E. A. Kushnareva; E. V. Zhiduleva; E. G. Malev; I. V. Antonova; M. L. Gordeev; E. A. Demchenko (Российский кардиологический журнал)
Aim.  To assess the  detection  rate  of infective endocarditis  (IE) in postoperative period in patients with aortic stenosis  (AS) and analyze the impact of late diagnosis on disease outcomes.Material and methods. A retrospective analysis of the register of 1764 patients with AS, formed on the basis  of transthoracic echocardiographic (echo)  tests  in2009-2011, was performed. During the 8-year follow-up period, 679 patients were operated  on;  IE  was  diagnosed  in  131  people.  Patients  were  divided  into subgroups depending  on the  valve morphology  and  the  time of IE verification before   or  after  surgery.   IE, first  detected  in  the  postoperative  period,  was considered as latent IE.Results. Among patients  with AS, the proportion of people  with IE was only 3,7%, however, pathomorphological examination revealed  IE signs in 19,3%. In 58,8% ofcases, IE was detected for the first time in the postoperative period. In 66,2% of cases,latent IE was diagnosed in patients with congenital heart disease (CHD) — bicuspidaortic valve (BAV). In the group of patients with known IE before surgery, there were lower levels of hemoglobin, erythrocytes and a higher level of creatinine. According to the results of a histological examination, inactive IE was diagnosed in 28% of cases. In 26,5% of patients  stage  3 activity IE was defined,  among  which latent course  was recorded in 16%. Single-agent antibiotic therapy (ABT) was carried out in 40,5% of patients, dual-agent ABT — in 50,0%, triple-agent — in 9,5%. The median duration of ABT was 14 days (7 to 42). The eight-year survival rate for patients with IE was 91,2%. Of the 9 deaths, only 5 (56%) had a diagnosis of IE before surgery.Conclusion. More than half of the patients operated on for AV defects  had a latent course  of IE and,  as  a  result,  late  diagnosis,  which could  affect  medium-term survival. Most of the people  with latent IE included in the analysis had CHD-BAV, which requires the development of IE preventive measures in this patient population. Various  approaches to  the  ABT of latent  IE in clinical practice   determine  the relevance  of additional  studies  aimed  at unification the  ABT approaches in this clinical setting.